A Modified Asynchronous PSO Algorithm - Tian, Daxin; Hu, Junjie; Xia, Haiying; Liu, He (2015 IEEE 12th Intl Conf on Ubiquitous Intelligence and Computing and 2015 IEEE 12th Intl Conf on Autonomic and Trusted Computing and 2015 IEEE 15th Intl Conf on Scalable Computing and Communications and Its Associated Workshops (UIC-ATC-ScalCom), 2015)
To analyze the convergence of PSO algorithm, a method based on two order constant coefficient recursive method is proposed in this paper. A new way to modify PSO and APSO algorithm achieved by adjusting the progress of algorithm is also proposed, thus forming MPSO and MAPSO algorithm, and this paper also presents Auto-regulative PSO algorithm which can automatically adjust parameters in the iterations. Ten basic functions are used for experiments to study the performance of the algorithms, and the results of experiments prove that Auto-regulative PSO algorithm and MAPSO are superior to MPSO and APSO respectively.